The World of Islam - Addison, James Thayer, 1887-1953 (Analecta Gorgiana, 2010)
This pamphlet is designed to help guide Churchmen and women in their reading on the Muslim world. At a time when, as Addison pointed out, Islam was throwing off the inertia of centuries and actively seeking to adopt the ways of the West, it was especially necessary to understand the beginnings, developments, and trends in that faith. Addison, who was one of the leading students of Islam in the Episcopal Church of his day, wrote this brief essay and appended it to descriptions of a few well selected books intended to give readers an understanding of the world of Islam.